Smart irrigation system using LoRA-based IoT devise / Muhammad Nizamuddin Abd Muttalib and Iman Hazwam Abd Halim - Abd Muttalib, Muhammad Nizamuddin; Abd Halim, Iman Hazwam (College of Computing, Informatics and Media, UiTM Perlis, 2023)
Agriculture plays the main role in a country's economy. Agriculture provides food and jobs to the community. In Malaysia, agriculture has been one of the main activities that contributes to income, especially to the people that stay in rural areas like villages. However, the method use is traditional and energy consuming. This article will explain the implementation of technology in the current traditional agriculture method. The aim is developing a smart irrigation system using a LoRa-based IoT device in order to help owners and farmers that used to monitor their crop manually. Using the LoRa increases the range covered compared to the previous wireless technology. Through the result gained from the project, it was clear that LoRa is better in an open space area. This study will test the functionality of the system and to test the network of LoRa in terms of distance, packet latency, and obstacle.